Analysis of electric field distribution within a microwave assisted thermal sterilization (MATS) system by computer simulation. (November 2016) - Luan, Donglei; Tang, Juming; Pedrow, Patrick D.; Liu, Frank; Tang, Zhongwei
Abstract: Microwave heating holds potential to improve food quality of low acid shelf-stable or chilled meals as compared to conventional thermal processes. Several thermal processes based on pilot-scale 915 MHz single-mode microwave assisted thermal sterilization (MATS) systems have received acceptances from regulatory agencies in USA. In this study a comprehensive computer simulation model was developed to study microwave distributions within waveguides and applicators of the MATS system. A three-dimensional model was developed based on Maxwell equations using the finite difference time-domain method. It was validated and then used to analyze electric field distribution in different parts of the MATS waveguide configuration and in a microwave heating cavity. Simulation results indicated that the TE10 mode was consistent within the waveguide elements. The dominant electric field component within the microwave heating cavity controlled the heating pattern in the food packages. Adjusting the dimension of the cavity in the dominant direction should help improve heating uniformity. Food packages immerged in water reduced the edge heating of packaged foods. Adjusting the phase of standing wave within the microwave heating cavity can improve the heating uniformity in the direction of the thickness. The information from this study should assist design of industrial systems with improved heating uniformity in food packages. Highlights: The propagation mode of microwave was consistent within MATS system. A standing wave formed at the middle of the microwave heating cavity. The phase of standing wave could be adjusted by changing the length of waveguide. The electric field distribution in y direction determines the heating pattern of food. The design principle of the MATS system was illustrated.